Evangelizar e politizar :O sentido da atuação da Igreja Católica com os sindicatos dos trabalhadores rurais no Seridó potiguar (1964-1979) - Silva, Maria Auxiliadora Oliveira da (2007)
The purpose of this work is to analyze the influence of the Catholic Church on rural worker s union in the Seridó potiguar region between 1964 to 1979. To the work developed by the Church is connected the beginning of worker s union in the Seridó region. In this way, this research tries to understand what is also the politic direction of the labor s union by means of the Cathólic Church that througt a process of creating Leagues have been looking for reinforcing and protecting catholicism as a way of maintaining its believers and distancing them from others movements such as Peasant League and the influence of Brazilian Communist Party. We use as sources oral narratives and newspaper A Folha , wich was published by the Parish Church of Caicó (RN) between 1954 to 1967. Some wrintten documents produced by worker s union from the Seridó region were also used